Encyclopedia of gay and lesbian popular culture - Prono, Luca; Gale Group (Westport, Conn. Greenwood Press, 2008)
Highlights the people, genres, and artistic works of the gay and lesbian community, and their contributions to popular culture.
Electronic reproduction.
Keywords: Homosexuality -- North America -- Encyclopedias; Homosexuality -- Great Britain -- Encyclopedias; Popular culture -- North America; Popular culture -- Great Britain; Electronic books